The impact of changes in methodology of participatory budgeting of Dąbrowa Górnicza on the quality of selected project - Majorek, Agnieszka (Research Papers of Wrocław University of Economics, 2018)
In recent years there has been a growing interest in tools that enable a dialogue between local authorities and members of local community, hence participatory budgeting has been gaining in popularity. The aim of the article is to examine conceptual and methodological changes in participatory budgeting in Dąbrowa Górnicza and the methods of completion of particular stages of the process. The article focuses on the diversity of methodologies of selecting projects and the process of projecting tasks. It contains an analysis of the transformation of participatory budgeting of Dąbrowa Górnicza and its impact on the quality of eventually selected projects, and the local development of specific districts. The introduction of new mechanisms in participatory budgeting is crucial to ensure that a participatory budget reflects real urban co-governance
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 502, s. 95-103
Keywords: evaluation; participatory budgeting; participation; ewaluacja; budżet obywatelski; partycypacja